2003
DOI: 10.21273/hortsci.38.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Basal Medium and Sucrose Concentration Influence Regeneration of Easter Lily in Ovary Culture

Abstract: Influences of culture media and sucrose concentrations on plant regeneration from Easter lily (Lilium longiflorum L. cv. Ace) ovary tissues were investigated. Pistils excised from unopened flower buds (3-5 cm long) were sectioned and cultured on either B-5 medium or Murashige and Skoog (MS) medium containing 2%, 5%, or 10% sucrose, with 1 mg·L-1 2,4-D and 2 mg·L-1 BA. Callus formation was most prolific on MS medium containing 5% sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
2
6
0
3
Order By: Relevance
“…A good response was also observed on several of the media where the auxin:cytokinin ratio was 1:1, such as 50 lmol L -1 each of 2,4-D and BA. These results were somewhat consistent with the observations of Boltenkov et al (2004) and Ramsey (2003) who found with Iris and Lilium, respectively, that the combination of 2,4-D and BA was effective at similar auxin : cytokin ratios of 1:1 or 2:1. More work needs to be conducted to optimise the long-term culture of D. excelsa callus, which has so far proven to be slow.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A good response was also observed on several of the media where the auxin:cytokinin ratio was 1:1, such as 50 lmol L -1 each of 2,4-D and BA. These results were somewhat consistent with the observations of Boltenkov et al (2004) and Ramsey (2003) who found with Iris and Lilium, respectively, that the combination of 2,4-D and BA was effective at similar auxin : cytokin ratios of 1:1 or 2:1. More work needs to be conducted to optimise the long-term culture of D. excelsa callus, which has so far proven to be slow.…”
Section: Discussionsupporting
confidence: 92%
“…Micropropagation techniques have also been widely used with success on a range of related monocotyledons such as those of the Iridaceae (Boltenkov et al 2004;Boltenkov and Zarembo 2005;Shibli and Ajlouni 2000;Shimizu et al 1997) and Liliaceae (Griesbach 1989;Ramsey et al 2003) that now have wide commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that concentrations of carbohydrates stimulate histodifferentiation (Ramsay et al 2003). In A. vera-cruz (Tejavathi et al 2007) and in A.…”
Section: Development and Maturation Of Somatic Embryosmentioning
confidence: 98%
“…There are a lot of studies which have been investigated about Lilium species propagated from scale by micropropagation and also in vitro regeneration from scales of Lilium [7][8][9][10][11]. These studies associated with plant growth regulators -such as auxin and cytokinin concentrations- [3,4,7,[12][13][14][15][16], light application [11,[17][18][19][20], scale position and explant size [7,12,17,21,22], sucrose concentration [7,11,12,[22][23][24]. There are no studies on micropropagation of L. candidum about effect of some antibiotic and fungicide applications.…”
mentioning
confidence: 99%